Image Processing and Restriction of Video Downloads Using Cloud - Hari Krishna, Yaram; Bharath Kumar, Kanagala; Maharshi, Dasari; Amudhavel, J (International Journal of Engineering and Technology, 2018)
Flower image classification using deep learning and convolutional neural network (CNN) based on machine learning in Tensor flow. Tensor flow IDE is used to implement machine learning algorithms. Flower image processing is based on supervised learning which detects the parameters of image. Parameters of the image were compared by decision algorithms. These images are classified by neurons in convolutional neural network. Video processing based on machine learning is used in restriction of downloading the videos by preventing the second response from the server and enabling the debugging of the video by removing the request from the user.
Keywords: Image detection; convolutional neural network (CNN); Machine learning; Video restriction; Debugging; deep neural network.